Trajetórias reveladas: as memórias formativas e a identidade do professor de História - Melo, Pedro Thiago Costa (2024)
The present Thesis, part of the Research Line School Practices and Public Policies of the Graduate Program in Education at the Federal University of Santa Maria (UFSM) and the Center for Studies on Memory and Education (Povo de Clio), analyzed the process of constructing the identity of the History Teacher through their autobiographies, captured by formative memorials. It had the following general research problem: how do the memories of History teachers present their formative journey and consequently their teaching identity? The general objective was to analyze formative memories, based on the autobiographical narratives of History teachers, in order to unveil the construction of their teaching identity. The specific objectives were delineated as follows: 1) to reflect on the theoretical and conceptual aspects that encompass the qualitative approach, research in education, biography, memory, and teaching identity; 2) to present the adopted methodology, content analysis; and 3) to analyze, from autobiographical accounts, specifically, the formative memories of History teachers and their teaching identity. Structurally, initially, the Thesis investigated the theoretical and conceptual aspects that underpinned it, including the qualitative approach, research in education, biography, memory, and teaching identity from authors such as Gadamer (1997), Santos (2020), Souza (2018), Gatt (2007), Xavier (1999), Esteban (2010), Nóvoa (2003), Finger (1988), Delory-Momberger (2012), Ferrarotti (2014), Arfuch (2010), Bourdieu (1986), Elias (1994), Passeggi (2011), Vicentini (2011), Josso (2006), Le Goff (2003), Rüsen (2009), Ricouer (2007), Halbwachs (1990), Chartier (2002), Brandão (2008), Peres (2009), Bose (1994), Tardif (2002), Melucci (2004), Ciampa (1987), Dubar (1997), and Garcia (2005). Then, the adopted methodology was detailed for its elaboration, based on the content analysis of the autobiographical narratives of History teachers, according to Bardin (1977). This process comprised stages, including pre-analysis, exploration of the material, treatment of results, and interpretation of data. This approach allowed for a detailed analysis of the experiences and trajectories of teachers, contributing to a deeper understanding of the formative process and the construction of the teaching identity in History. Methodologically, it is a qualitative research, which appropriated the autobiographical method (formative memorial - as a tool for capturing formative memories) and bibliographic sources. With all this, we reached the conclusion (Thesis of the research) that the formation of the identity of the History teacher is intrinsically linked to a complex interaction of various contexts, such as academic trajectory (including the university environment and influences of authors), life trajectory (involving family aspects, social context, school experiences, and individual preferences), and professional trajectory (including internships and effective teaching practice). These elements play a significant role in shaping the identity of History teachers.